Novel composite fibers coated with birnessite layer - Bondar, Yu.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
New composite material is synthesized by the in situ formation of a manganese dioxide layer on the surface of modified polyacrylonitrile fibers. Scanning electron microscopy, infra-red and X-ray diffraction analyses confirmed the formation of birnessite (δ-MnO2) on fibers' surface, which forms a compact layer consisted of rounded nanoaggregates. The testing of composite fibers in the catalytic oxidation of divalent iron in a solution has shown their high efficiency.